1984
DOI: 10.1002/tea.3660210102
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mediating factors of moral reasoning in science education

Abstract: The purpose of this research was to examine how science content knowledge, moral reasoning ability, attitudes, and past experiences mediate the formation of moral judgments on environmental dilemmas. The study was conducted in two phases using environmental science majors and nonscience majors of college age. Phase One determined if environmental science majors exhibited higher levels of moral reasoning on nontechnical environmental social issues than on general social issues and examined the extent to which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
16

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 17 publications
4
45
0
16
Order By: Relevance
“…The authors suggested in very clear terms that moral development is a factor of interest when assessing decision-making strategies on SSI. Their research findings also provided supporting evidence for earlier work that revealed explicit links between college students' levels of moral reasoning and decision making on SSI irrespective of their science content knowledge level of sophistication (Zeidler & Schafer, 1984).…”
Section: Thematic Areas Of Recent Research Connected To Ssisupporting
confidence: 83%
See 3 more Smart Citations
“…The authors suggested in very clear terms that moral development is a factor of interest when assessing decision-making strategies on SSI. Their research findings also provided supporting evidence for earlier work that revealed explicit links between college students' levels of moral reasoning and decision making on SSI irrespective of their science content knowledge level of sophistication (Zeidler & Schafer, 1984).…”
Section: Thematic Areas Of Recent Research Connected To Ssisupporting
confidence: 83%
“…Several researchers have corroborated the importance of this perspective in the context of SSI (Korpan et al, 1997;, 2005Zeidler & Schafer, 1984). For example, Sadler and Zeidler (2005) not only concluded that individuals may rely on emotions for the resolution of SSI, but that informal reasoning based on emotion was often equivalent to strictly cognitive approaches to decision making in terms of logical constructs such as internal consistency and coherence.…”
Section: Thematic Areas Of Recent Research Connected To Ssimentioning
confidence: 97%
See 2 more Smart Citations
“…Zeidler and Schafer (1984) reported that comprehension of science, positive attitudes, and a strong commitment toward a particular issue were all positively related to the level of moral reasoning college students used to make social judgments. Fleming (1986a) found that adolescents primarily viewed science and technology based issues in ways that stressed the social aspects of the issue.…”
Section: Introductionmentioning
confidence: 99%